Collaborative Digital Governance in the Management of Value-Based Education - Julizar Idris (Jurnal Polisci, 2026)
Background. Digital transformation has driven changes in education governance towards a more collaborative, adaptive, and technology-based system. Purpose. The purpose of this study is to analyze the concept of collaborative digital governance in the management of value-based education through the Systematic Literature Review (SLR) approach. Method. Data was obtained from various scientific articles derived from databases such as Scopus, ScienceDirect, SpringerLink, Emerald Insight, Taylor & Francis, and Google Scholar. The research process followed the PRISMA stages, and the data analysis used content analysis. Results. The results of the study show that collaborative digital governance is an educational governance model that integrates multi-stakeholder collaboration with digital technology in the decision-making process and the management of educational services. This approach can increase effectiveness, transparency, and public participation in educational governance. However, its implementation still faces challenges, including digital divides, limited infrastructure, low digital literacy, and ethical and data security issues. Conclusion. Value-based education is an important foundation in maintaining the humanistic dimension of education in the digital era through strengthening moral values, responsibility, and sustainability. Value-based collaborative digital governance can be a strategic approach in creating an inclusive, adaptive, and sustainable education system.